Mergers and Acquisitions in the Indian Context : A Valuation Perspective for the Indian Pharmaceutical Industry - Gala, Chintan; Bhattacharya, Mousumi (Indian Journal of Finance, 2022)
Mergers and acquisitions (M&A) as a strategy has been used increasingly by the corporate sector to gain a competitive advantage. Mergers and acquisitions (M&A) help a firm gain new customer bases, enter new markets, gain access to new technologies, and help achieve cost reduction. In today’s time, firms try to achieve synergistic gains through M&As. This study aimed to: a) understand if prices paid by acquiring firms reflected synergistic gains and b) observe value created for shareholders of the acquiring firms. The study used secondary data for the purpose of research. A neural network model was built to scrutinize the impact of the selected variables on the value of the mergers and acquisitions (M&A) deal. An event study was carried out to assess value creation for shareholders of the acquiring firm. The study found that an acquiring firm generally paid more during the M&As compared to the synergistic gains it realized post-acquisition. Additionally, there was no value creation for the acquiring firm’s shareholders. The neural network model from this study, with appropriate variables, can be used to predict the price of an M&A deal. The study will benefit the stakeholders of pharmaceutical firms to make informed decisions regarding mergers and acquisitions.